A new echiuran-associated snapping shrimp (Crustacea: Decapoda: Alpheidae) from the Indo-West Pacific - Anker, Arthur; Komai, Tomoyuki; Marin, Ivan N. (Zootaxa, 2015)
Alpheus echiurophilus sp. nov. (Crustacea: Decapoda: Caridea: Alpheidae) is described based on material from Japan (Ryukyu Islands) and Vietnam (Nha Trang Bay); an additional, morphologically slightly different specimen from Madagascar (Nosy-Bé) is preliminarily referred to A. cf. echiurophilus sp. nov., awaiting collection of additional material and/or genetic comparison. All specimens of the new species were collected from burrows of thalassematid echiurans, either on intertidal and shallow subtidal sand-mud flats or in the mixed sand-gravel-rock intertidal. Alpheus echiurophilus sp. nov. belongs to the A. leviusculus species group, being morphologically closest to the Indo-West Pacific A. leviusculus Dana, 1852, A. hululensis Coutière, 1905, A. ladronis Banner, 1956, and the western Atlantic A. zimmermani Anker, 2007. The new species can be separated from all of them by a combination of morphological characters and also appears to have a diagnostic colouration.